A three dimensional age estimation using cone beam CT in Malaysian population / Muhammad Khan Asif - Muhammad Khan, Asif (2020)
Forensic odontology plays a vital role in the age estimation and identification process during criminal investigations. Forensic science in the past have mainly employed two-dimensional (2D) radiographic assessment of developmental and physiological age related dental parameters for age estimation. However, 2D radiograph doesn’t represent the three-dimensional (3D) anatomical structures. Rapidly evolving CBCT imaging modality can be effectively employed in forensic sciences to overcome the limitations of 2D imaging. The current study aimed to develop a novel method of dental age estimation using 3D surface area analyses of root apices of the developing permanent maxillary canines and mandibular third molars among Malaysian population using CBCT data. Two new and validated dental age estimation regression equations were developed. The first regression equation was developed for Malaysian children aged 7 to 14 years by assessing the relationship between chronological age and surface area of the developing maxillary canine apex. Variations based on ethnicity (Malay/Chinese), gender and status of root development (open/closed) were also investigated in terms of fit to the age estimation model. The training sample of 191 permanent maxillary canines was selected from the CBCT images belonging to 100 Malays and 91 Chinese. Moreover, an independent validation sample of 96 permanent maxillary canines was also selected. Multiple linear regression analysis was used to derive an age estimation model using chronological age as a dependent variable and surface area of the maxillary canines apices, ethnicity, gender and status of the root development (open/closed apices) as predictor variables. A strong correlation (r = 0.978) was observed between chronological age and the predictor variables. 95.6 % of the variation in age was explained by the surface area of canine apex, gender and status of the root development (open/closed apices). However, ethnicity did iv not contribute to the fit of age estimation model. Mean absolute error (MAE) value of 0.30 was observed when tested on an independent validation sample. The second regression equation was developed for Malaysian juveniles and young adults aged 13 to 24 years by assessing the relationship between chronological age and surface area of the developing mandibular third molars apices. The training sample of 128 intact mandibular third molars was selected from the CBCT images belonging to 66 Malays and 62 Chinese. In addition, 55 mandibular third molars were selected as a validation sample. Multiple linear regression analysis was used to derive an age estimation model using chronological age as a dependent variable and surface area of the mandibular third molars apices, ethnicity, gender and status of the root development (open/closed apices) as predictor variables. A strong inverse correlation (r = 0.95) was observed between chronological age and all the predictor variables. The results showed that 89.6% of the variation in age can be explained by the predictor variables. MAE value of 0.822 was observed when the derived regression equation was tested on the independent validation sample. In conclusion, 3D surface area analysis of the developing root apices can be used as a reliable method for age estimation in Malaysians. Keywords: CBCT; Age estimation; Three-dimensional; Malaysian.